Pop When the World Falls Apart : Music in the Shadow of Doubt - Weisbard, Eric (Book collections on Project MUSE., 2012)
Hearing Elvis Presley, Bob Dylan once said, was "like busting out of jail." But what happens when popular music isn't as simple as rock-and-roll rebellion? How does pop respond to such events as a decade-long war in Iraq and Hurricane Katrina? In Pop When the World Falls Apart, a diverse array of music writers, scholars, and enthusiasts reflect on popular music's role--as commentary, as refuge, and as rallying cry--in times of military conflict, social upheaval, and cultural crisis. Drawn from presentations at the annual Experience Music Project Pop Conference--hailed by Robert Christgau as "the best thing that's ever happened to serious consideration of pop music"--The essays in this book include inquiries into the sonic dimension of war in Iraq; the cultural life of jazz in post-Katrina New Orleans; Isaac Hayes's reappropriation of a country song, "By the Time I Get to Phoenix," as a symbol of black nationalism; and punk rock pranks played on record execs looking for the next big thing in central Virginia. Offering a diverse range of voices, perspectives, and approaches, this volume mirrors the eclecticism of pop itself